1997
DOI: 10.1007/s004180050149
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of S-100 protein and its subunits in bovine exocrine glands

Abstract: The distribution of S-100 protein and its alpha- and beta-subunits in bovine exocrine glands was studied by indirect immunohistochemistry. The entire spectrum of salivary glands, glands of the respiratory tract, intestinal glands, male and female genital glands, and skin glands was examined. S-100 and its beta-subunit were identified in most serous secretory cells of mixed salivary glands, although secretory acini in some serous glands remained unreactive for these antigens. Mucous cells were constantly negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Furthermore, they confirm that S100 cannot be regarded as a nervous-system-specific protein, as previously thought (for a review, see Zomzely-Neurath and Walker 1980). Several studies have indicated that S100 plays a role in the secretion processes of exocrine and endocrine epithelia (Vanstapel 1986;Uchida and Endo 1989;Donato 1991;Lauboeck and Egerbacher 1997): it transduces calcium signals into biological responses by reversibly binding calcium and modulating the activity of the other proteins involved in the secretion processes (Haimoto et al 1987;Van Eldik and Zimmer 1988;Fano et al 1993;Gallego et al 1996). There is also evidence that the α subunit of S100 is localized in cells specifically involved in the regulation of pH, water, and electrolytes.…”
Section: Resultssupporting
confidence: 67%
“…Furthermore, they confirm that S100 cannot be regarded as a nervous-system-specific protein, as previously thought (for a review, see Zomzely-Neurath and Walker 1980). Several studies have indicated that S100 plays a role in the secretion processes of exocrine and endocrine epithelia (Vanstapel 1986;Uchida and Endo 1989;Donato 1991;Lauboeck and Egerbacher 1997): it transduces calcium signals into biological responses by reversibly binding calcium and modulating the activity of the other proteins involved in the secretion processes (Haimoto et al 1987;Van Eldik and Zimmer 1988;Fano et al 1993;Gallego et al 1996). There is also evidence that the α subunit of S100 is localized in cells specifically involved in the regulation of pH, water, and electrolytes.…”
Section: Resultssupporting
confidence: 67%
“…The cytosol in human submandibular gland IDs contains carbonic anhydrase isozyme VI (Ogawa et al, 1993), whereas carbonic anhydrase isozyme III is present in the same gland in cows (Asari et al, 1993). Lauboeck and Egerbacher (1997) report that in IDs in bovine submandibular gland there is strong histochemical staining for the calcium-binding protein, S-100, and its ␤ subunit. Lee et al (1993) observed S-100␤ in the same location in human salivary glands.…”
mentioning
confidence: 92%
“…The alpha subunit of 8-100 was related to cells that are highly involved in pH, electrolyte, and water regulation (Molin et aI., 1985). It has been suggested that S100-alpha is related to resorption and secretion in exocrine glands (Lauboeck and Egerbacher, 1997). The variable intensity of the reaction seen in this study may indicate different degrees of activity of the duct cells or may indicate different types of cells.…”
Section: Basal Cellsmentioning
confidence: 52%
“…The resorption and secretion in exocrine glands have been related to 8100 proteins (Lauboeck and Egerbacher, 1997). 8-100 is a group of closely related, small, acidic Ca2+-binding proteins (8-100aO, 8-100a and 8-1OOb).…”
Section: Introductionmentioning
confidence: 99%